Preparedness of aesthetic medicine professionals for emergency scenarios: the SIMED–AGORÀ cross-sectional study - Stirparo, Giuseppe; Vinci, Antonio; D'Angelo, Marta; Spadotto, Lorenzo; Bardhi, Dorian; Arrigoni, Francesca; Belletti, Stefania; Cavallini, Maurizio; Papagni, Marco; Fagoni, Nazzareno (Aesthetic Medicine, 2026)
Background: Emergency management in aesthetic medicine is a fundamental component of patient safety. Despite the increasing demand for outpatient aesthetic procedures, the literature provides limited evidence on the actual preparedness of aesthetic physicians in managing acute medical emergencies not directly related to procedures1. This study aimed to evaluate the knowledge and competence level of aesthetic medicine professionals in handling emergencies and urgent-care scenarios, with the goal of identifying potential areas for educational improvement.Methods: A 22-item questionnaire (7 demographic and 15 clinical questions) was developed within the SIMED–AGORÀ project. Fifty-six aesthetic physicians participated. A competence threshold of 12/15 (80%) correct answers was predefined. Data were analyzed using STATA 18 software; comparisons between professional areas were performed with one-way ANOVA followed by Tukey’s post-hoc test, and categorical variables were analyzed using χ² tests.Results: The mean age of participants was 35.8 years (SD 7.4), and 42.8% had completed a postgraduate master’s in aesthetic medicine. Eighty-nine percent had attended BLSD courses, and 30% had completed ACLS training. The mean total score was 10.6 (SD 2.5). Physicians with ACLS training were significantly more likely to reach the competence threshold (OR 3.6; 95% CI 1.2–11.8; p = 0.03). Significant differences emerged among professional areas (F(5,50)=10.62; p < 0.001), with higher scores in the emergency–urgent-care group. Overall, 80.4% expressed interest in specific training on emergencies in the aesthetic-medicine setting.Conclusions: Aesthetic physicians demonstrated satisfactory basic competence, but important gaps persist in pharmacologic management and systemic emergency response. Integrating specific intermediate training modules—bridging BLSD and ACLS—could improve preparedness and enhance both safety and quality of care in aesthetic medicine.